2021
DOI: 10.1155/2021/4012893
|View full text |Cite
|
Sign up to set email alerts
|

Differential HLA Association of GAD65 and IA2 Autoantibodies in North Indian Type 1 Diabetes Patients

Abstract: The human leucocyte antigen (HLA) association with type 1 diabetes (T1D) is well known but there are limited studies investigating the association between β-cell autoantibodies and HLA genes. We evaluated the prevalence of GAD65 and IA-2 autoantibodies (GADA and IA2A) in 252 T1D patients from North India and investigated the genetic association of GADA and IA2A with HLA class I and class II genes/haplotypes. GADA and IA2A were detected in 50.79% and 15.87% of T1D patients, respectively, while only 8.73% had bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…[15][16][17] Further, HLA-DRB1*03-DQA1*05-DQB1*02 haplotype is reported to be strongly associated with the presence of GADA in T1D patients. 19,20,[26][27][28] A recent study that investigated the association between epitope-specific GADA and the HLA-DR-DQ haplotypes revealed that T1D-susceptible HLA haplotypes, particularly DR3 positive haplotypes, associate strongly with GAD65Ab multiepitope positivity, suggesting that an important pathological mechanism in T1D might involve the presentation of GAD65 peptides by both HLA-DR and HLA-DQ molecules. 29 The present study was carried out to characterize the GAD65 epitopes possibly presented by HLA-DR3/DQ2 molecules to CD4 T cells and compare them between T1D patients and HC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[15][16][17] Further, HLA-DRB1*03-DQA1*05-DQB1*02 haplotype is reported to be strongly associated with the presence of GADA in T1D patients. 19,20,[26][27][28] A recent study that investigated the association between epitope-specific GADA and the HLA-DR-DQ haplotypes revealed that T1D-susceptible HLA haplotypes, particularly DR3 positive haplotypes, associate strongly with GAD65Ab multiepitope positivity, suggesting that an important pathological mechanism in T1D might involve the presentation of GAD65 peptides by both HLA-DR and HLA-DQ molecules. 29 The present study was carried out to characterize the GAD65 epitopes possibly presented by HLA-DR3/DQ2 molecules to CD4 T cells and compare them between T1D patients and HC.…”
Section: Discussionmentioning
confidence: 99%
“…For GADA screening, we used commercially available ELISA assay kit, ElisaRSR™GADAb kit (RSR Ltd., United Kingdom). The GADA was estimated by following the protocol as described previously 19 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations